2021
DOI: 10.5194/acp-21-6155-2021
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Firework impacts on air quality in Metro Manila, Philippines, during the 2019 New Year revelry

Abstract: Abstract. Fireworks degrade air quality, reduce visibility, alter atmospheric chemistry, and cause short-term adverse health effects. However, there have not been any comprehensive physicochemical and optical measurements of fireworks and their associated impacts in a Southeast Asia megacity, where fireworks are a regular part of the culture. Size-resolved particulate matter (PM) measurements were made before, during, and after New Year 2019 at the Manila Observatory in Quezon City, Philippines, as part of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…In our study, inorganic pollutants played a more important role than meteorological parameters and VOCs in the distributions of both abundant and rare taxa. This finding suggested the critical position of human activities in affecting the communities of airborne microbes [ 20 ] due to fireworks and other human activities that have been indicated as important drivers in changing air quality [ 45 , 46 ], especially water‐soluble ions and elements [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, inorganic pollutants played a more important role than meteorological parameters and VOCs in the distributions of both abundant and rare taxa. This finding suggested the critical position of human activities in affecting the communities of airborne microbes [ 20 ] due to fireworks and other human activities that have been indicated as important drivers in changing air quality [ 45 , 46 ], especially water‐soluble ions and elements [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…We considered if seasonal differences in PM in Metro Manila could arise from emissions that exhibit seasonal cycles. However, seasonal differences in meteorology may be seen as the chief driver of seasonal trends in PM due to the following reasons: (1) sampling was conducted within Metro Manila with the main PM sources including vehicular emissions, industry, cooking, sea salt, and waste processing, [12][13][14][15][16][17][18][19] which are consistent throughout the year given the tropical urban setting; (2) urban emissions are expected to be consistent throughout the year as Metro Manila has a tropical climate with relatively stable year-round temperatures (primarily between 25-30 C), 35 thus emissions from heating or cooling remain consistent throughout the year; and (3) although the Philippines does receive long-range transport from East Asia and the Maritime Continent, 13,35,40,[56][57][58] Metro Manila itself is largely insulated by mountains and ocean from these sources. Previous work has shown that the long-range transport of PM to the Philippines is naturally transient and PM levels return to normal values aer episodes of long-range transport.…”
Section: Consistent Pm Across Wet and Dry Seasonsmentioning
confidence: 99%
“…Metro Manila, Philippines is a rapidly developing megacity lacking strict air quality monitoring and regulation even though there are many PM sources including vehicular, industrial, rework, and cooking emissions as well as secondary formation, based on previous source apportionment work. [12][13][14][15][16][17][18][19] Recent size-resolved measurements focusing on source apportionment showed that most of the PM mass in Metro Manila resides within the submicrometer range. 14 Though PM levels (i.e., mass concentrations) are expected to be lower in the wet season (May-October) than the dry season (November-April) due to wet scavenging by precipitation, Kim Oanh et al 20 revealed that PM levels in Metro Manila are remarkably consistent between wet (44 mg m À3 ) and dry (43 mg m À3 ) seasons, later corroborated by Simpas et al 21 Potential contributors towards the seasonally consistent PM include inefficient scavenging, seasonal emissions, and meteorological inuences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also highlighted significant health risks associated with highly concentrated fireworks burning. Scholars analyzed the effect of fireworks burning on air quality and found that fireworks increased the concentration of aerosol, resulting in the deterioration of air quality with elevated concentrations of main pollutants [ 1 , 16 , 27 , 28 , 29 , 30 ]. By monitoring the changes in particulate matter in Nanning, Li et al [ 31 ] found that fireworks burning was the main source of particulate matter.…”
Section: Introductionmentioning
confidence: 99%